Chlorophyll Production in the Amundsen Sea Boosts Heat Flux to Atmosphere and Weakens Heat Flux to Ice Shelves - Twelves, A. G.; Goldberg, D. N.; Holland, P. R.; Henley, S. F.; Mazloff, M. R.; Jones, D. C. (John Wiley & Sons, 2024)
The Amundsen Sea in West Antarctica features rapidly thinning ice shelves, large polynyas, and sizable spring phytoplankton blooms. Although considerable effort has gone into characterizing heat fluxes between the Amundsen Sea, its associated ice shelves, and the overlying atmosphere, the effect of the phytoplankton blooms on the distribution of heat remains poorly understood. In this modeling study, we implement a feedback from biogeochemistry onto physics into MITgcm-BLING and use it to show that high levels of chlorophyll—concentrated in the Amundsen Sea Polynya and the Pine Island Polynya—have the potential to increase springtime surface warming in polynyas by steepening the attenuation profile of solar radiation with depth. The chlorophyll-associated warm anomaly (on average between +0.2C and +0.3C) at the surface is quickly dissipated to the atmosphere, by increases in longwave, latent and sensible heat loss from open water areas. Outside of the coastal polynyas, the summertime warm anomaly leads to an average sea ice thinning of 1.7 cm across the region, and stimulates up to 20% additional seasonal melting near the fronts of ice shelves. The accompanying cold anomaly, caused by shading of deeper waters, persists year-round and affects a decrease in the volume of Circumpolar Deep Water on the continental shelf. This cooling ultimately leads to an average sea ice thickening of 3.5 cm and, together with associated changes to circulation, reduces basal melting of Amundsen Sea ice shelves by approximately 7% relative to the model scenario with no phytoplankton bloom.